Factor VIII as a potential player in cancer pathophysiology. (11th January 2022) - Walker, Gillian E.; Merlin, Simone; Zanolini, Diego; Vandoni, Andrea; Volpe, Alessandro; Gaidano, Gianluca; Valente, Guido; Olivero, Martina; Follenzi, Antonia
Abstract: Background: Trousseau sign was the first demonstration of a close relationship between cancer and thrombosis. Currently, venous thromboembolism (VTE) is five to six times more likely to occur in cancer patients, whereas there is a greater risk of cancer diagnoses following thromboses. In considering novel players, factor VIII (FVIII), an essential coagulation cofactor with emerging extracoagulative functions, has been identified as an independent VTE risk factor in cancer; however, the basis of this increase is unknown. Objective: To investigate the possible direct expression and secretion of FVIII by cancer cells. Methods: Bladder cancer, with a high VTE risk, and normal bladder tissue and epithelium, were used to investigate FVIII. Factor VIII protein and secretion were examined in bladder cancer cell lines. Expanding to other cancers, the Cancer Cell line Encyclopedia database was used to analyze FVIII, tissue factor, FV, FVII, FIX, FX, and von Willebrand factor (VWF) mRNA in 811 cell lines subdivided according to origin. Factor VIII protein synthesis, secretion, and bioactivity were investigated in a profile of cancer cell lines of differing origins. Results and conclusions: Although expressed in the normal bladder epithelium, FVIII mRNA and protein were higher in matched bladder neoplasms, with synthesis and secretion of bioactive FVIII evident in bladder cancer cells. This can be extended to other cancer cell lines, with a pattern reflecting the tumor origin, and that is independent of VWF and other relevant players in the coagulation cascade. Here, evidence is provided of a possible independent role for FVIII in cancer‐related pathophysiology.